Evangelicals and the neoliberal urban apparatus: governing populations and peripheral urban territories (Geografares, 2022)
This article presents the partial results of an ongoing doctoral research on the relations between evangelical churches in the favelas and peripheries of Rio de Janeiro and neoliberalism. The objective is to know the role played by these churches in neoliberal governmentality. Therefore, religion is interpreted as a phenomenon of legitimation of power (Durkheim, Berger, Bourdieu and Weber) and neoliberalism as a form of government of individuals (Foucault and Dardot and Laval). The article also uses some preliminary data from an ethnography that I have been conducting in the city of Rio de Janeiro and secondary data from other publications. The partial results indicate that some evangelical churches are part of a heterogeneous and articulated set of governmentalities that I have called neoliberal urban device and that include modes of subjectivation, militarization, favelas removal, drug trafficking and militias.